Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the derivative of the function [tex]\( g(x) = \sqrt{x^3} + 2x^2 \)[/tex], we will proceed step-by-step.
Step 1: Rewrite the function [tex]\( g(x) \)[/tex]
Rewrite [tex]\( \sqrt{x^3} \)[/tex] as [tex]\( (x^3)^{1/2} = x^{3/2} \)[/tex].
Thus,
[tex]\[ g(x) = x^{3/2} + 2x^2 \][/tex]
Step 2: Differentiate each term separately
1. Differentiating [tex]\( x^{3/2} \)[/tex]:
[tex]\[ \frac{d}{dx} x^{3/2} = \frac{3}{2} x^{(3/2) - 1} = \frac{3}{2} x^{1/2} \][/tex]
2. Differentiating [tex]\( 2x^2 \)[/tex]:
[tex]\[ \frac{d}{dx} 2x^2 = 2 \cdot 2x = 4x \][/tex]
Step 3: Combine the derivatives
Add the derivatives of both terms to get the derivative of the entire function:
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
So, after calculating, the derivative of [tex]\( g(x) \)[/tex] is:
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
Step 4: Match the correct answer choice
From the given answer choices:
a. [tex]\( g'(x) = \frac{3}{2} x^{-1/2} + 4x \)[/tex]
b. [tex]\( g'(x) = \frac{3}{2} x^{1/2} + 4x \)[/tex]
c. [tex]\( g'(x) = \frac{3}{2} x^{1/2} + 2x \)[/tex]
d. [tex]\( g'(x) = \frac{3}{2} x^{-1/2} + 2x \)[/tex]
The correct choice is (b):
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
Therefore, the derivative of [tex]\( g(x) = \sqrt{x^3} + 2x^2 \)[/tex] is choice b.
Step 1: Rewrite the function [tex]\( g(x) \)[/tex]
Rewrite [tex]\( \sqrt{x^3} \)[/tex] as [tex]\( (x^3)^{1/2} = x^{3/2} \)[/tex].
Thus,
[tex]\[ g(x) = x^{3/2} + 2x^2 \][/tex]
Step 2: Differentiate each term separately
1. Differentiating [tex]\( x^{3/2} \)[/tex]:
[tex]\[ \frac{d}{dx} x^{3/2} = \frac{3}{2} x^{(3/2) - 1} = \frac{3}{2} x^{1/2} \][/tex]
2. Differentiating [tex]\( 2x^2 \)[/tex]:
[tex]\[ \frac{d}{dx} 2x^2 = 2 \cdot 2x = 4x \][/tex]
Step 3: Combine the derivatives
Add the derivatives of both terms to get the derivative of the entire function:
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
So, after calculating, the derivative of [tex]\( g(x) \)[/tex] is:
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
Step 4: Match the correct answer choice
From the given answer choices:
a. [tex]\( g'(x) = \frac{3}{2} x^{-1/2} + 4x \)[/tex]
b. [tex]\( g'(x) = \frac{3}{2} x^{1/2} + 4x \)[/tex]
c. [tex]\( g'(x) = \frac{3}{2} x^{1/2} + 2x \)[/tex]
d. [tex]\( g'(x) = \frac{3}{2} x^{-1/2} + 2x \)[/tex]
The correct choice is (b):
[tex]\[ g'(x) = \frac{3}{2} x^{1/2} + 4x \][/tex]
Therefore, the derivative of [tex]\( g(x) = \sqrt{x^3} + 2x^2 \)[/tex] is choice b.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.